A sobrevida de Graciliano Ramos e Ricardo Reis nas ficções de Silviano Santiago e José Saramago - Oliveira, Juliana Prestes de (2016)
This work intends to comparatively investigate two contemporary literary works, being these Brazilian writer Silviano Santiago's Em liberdade (1994) and Portuguese writer José Saramago's O ano da morte de Ricardo Reis. The analysis's focus is mainly to elucidate the way which both protagonists' figuration is done, respectively, Graciliano Ramos and Ricardo Reis (Fernando Pessoa's heteronym), and how it serves to feed the literary survival of these two historical figures from each country's literature. For this, we did the individual study of each novel, looking specially for the narrator and the protagonist, and later their figurations' comparison, in order to keep track of thematic approximations and deviation that make easier to understand each protagonist's human format, if they remain the same through the whole plot, as well as, through this, to think literature critical relation with the historical-social context. Thereby, it was important to pay attention to the perspectives that show up and are related in the narratives, interconnected to the narrators and characters' voices, and they contribute to the construction and the act of problematize of each protagonist's identity. With the comparative analysis of Reis and Ramos's trajectories, based on the theories about dialogism, focalization, perspectives and characters' figuration, from the researchers Mikhail Bakhtin, Gérard Genette, Ansgar Nüning and Carlos Reis, respectively, we can define who are these protagonists, their ways to live among the others and to position themselves into the world, we comprehend in a better way, by the end, the thematic implications of each novel's production in connection to their historical and literary contexts.